PERTUMBUHAN BEBERAPA ISOLAT MIKROBA DARI BERBAGAI LIMBAH INDUSTRI PADA BENZAMIDA - Nunik Sulistinah; Bambang Sunarko (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Twenty five microbes could be isolated from industrial effluents.Seven isolates of those examined microbes were able to grow on benzamide as sources of carbon,energy,and nitrogen..The highest growth on benzamide was shown by bacterial isolate D1.Besides on benzamide, isolate D1 could grow on acetamide,acrylamide, benzamide,nicotinamide and propionamide, respectively.. On carboxylic acids, however isolate D1 could grow only on acetic acid, propionic acid, and benzoic acid as carbon and energy sources.When isolate D1 grew on 40 mM benzamide, the doubling time(ȷ was 6 h 40 minutes, the specific growth rate () was 0,046 h' the attained maximum cell biomass was 4.96 g cell dry weigtAiter medium, and the yield coefficient (Y) was 124 g cell dry weight/mole benzamide.